The Effect Of Family Support On Postpartum Depression : Scoping Review - Navantri Muliyani; Endang Koni Suryaningsih (Universitas Muhammadiyah Surakarta, 2023)
Abstract. Typically, a mother with postpartum depressive disorder is depressed and has suicidal thought. One of the factors that contributes to emotional stress is relationships with family. Mother's unstable emotions during the postpartum period may affect on the baby's growth besides the mother. Scoping review of existing scientific evidence on postpartum maternal mental health is the goal of this study. Using the Arksey and O’Malley's (2005) framework and the PRISMA-ScR checklist, this research applied a scoping review. In this study, PubMed, Science Direct, and ResearchGate were used for literature searches. The terms